2017
DOI: 10.1007/s41465-017-0045-0
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory Training in Adolescents Decreases Laboratory Risk Taking in the Presence of Peers

Abstract: Adolescence is a period of heightened risk-taking relative to both adulthood and childhood, due in part to peers' increased influence on adolescent decision making. Because adolescents' choices have harmful consequences, there is great interest in specific interventions that might attenuate risk taking. We hypothesized that it might be possible to reduce adolescent risk taking through an intervention targeting the ability/tendency to engage cognitive control processes. While some studies of Working Memory Trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Additional related work includes Rosenbaum et al (2017), who found some evidence that training adolescents in working memory decreased their risk taking behavior in a hypothetical gambling task. A potential explanation for the link between working memory and risk taking is that improved working memory accelerates executive function development and therefore reduces risk taking.…”
Section: Skillsmentioning
confidence: 99%
“…Additional related work includes Rosenbaum et al (2017), who found some evidence that training adolescents in working memory decreased their risk taking behavior in a hypothetical gambling task. A potential explanation for the link between working memory and risk taking is that improved working memory accelerates executive function development and therefore reduces risk taking.…”
Section: Skillsmentioning
confidence: 99%
“…Furthermore, here, we show that some psychological methods can increase pro-security behaviours, such as rewarding and penalizing security-related behaviours, using novel polymorphic security warnings, and using psychological methods to increase thinking about future consequences of actions. In addition, there are cognitive training methods, including working memory training, that help reduce impulsivity, risk taking and procrastination in the general population (Rosenbaum et al, 2017;Peckham and Johnson, 2018). Such cognitive training methods can be used to ameliorate these behavioural traits and help improve cybersecurity behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] These games have been used not only for education, [13][14][15] but also for enhancing human skills such as working memory, executive function, and cognition. [16][17][18][19][20][21][22][23] While there are numerous numbers of studies reporting on improvement of working memory and executive functions after an intervention [16][17][18][19][20][24][25][26][27][28][29][30][31][32][33][34] (see reviews 35,36 ), the effect of training with a serious game on spatial cognition has received relatively less attention. Nevertheless, studies suggest that spatial cognition is commonly enhanced by repeated exercises of some serious games.…”
Section: Introductionmentioning
confidence: 99%